Traditional Chinese Economic Thought and Its Inspiration to Cultural Economy (Journal of Global Humanities and Social Sciences, 2026)
China’s 5,000-year civilization is replete with profound economic philosophies that have historically guided its socioeconomic evolution. This study systematically examines seven economic laws and seven governance strategies inherent to China’s traditional economic paradigm—a body of wisdom accumulated through empirical practices over history, providing trans-generational insights for socioeconomic governance. By identifying five synergistic policy mechanisms that elucidate complex policy interactions, this study applies the Four Dimensions-Nine Domains framework from Guanzi to construct a novel economic paradigm. This analytical framework proposes a governance model that moves beyond conventional reductionist analytical frameworks, embodying the integration of theoretical principles and pragmatic applications. It thereby provides a methodological innovation pathway for cultural economy studies under the purview of traditional Chinese economic philosophy.